2022
DOI: 10.1021/acsmedchemlett.2c00094
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NOX2 via p47/phox-p22/phox Inhibition with Novel Triproline Mimetics

Abstract: On the basis of the knowledge that the proline-rich hot spot PPPRPP region of P( 151)PSNPPPRPP( 160), an oligopeptide derived from the cytosolic portion of p22 phox (p22), binds to the single functional bis-SH3 domain of the regulatory protein p47 phox (p47), we designed a mimetic of the tripeptide PPP based on NMR and X-ray crystallographic data for the p22(151−161) peptide PPSNPPPRPPA with a peptide construct. Incorporation of the synthetic pseudo-triproline mimetic Pro-Pro-Cyp in a molecule derived from mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 53 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…While the straight SH3A domain-swapped dimer observed in the crystal structure of the p47phox–p22phox complex (pdb entry 1OV3 ) (Figure E) showed a better fit to the data, some discrepancies were still observed (SI Figure S1B). In the recent crystal structure of a p47phox–p22phox complex with an A200G mutation, the domain swapping is not present (pdb entry 7YXW ). Interestingly, in this structure the crystal packing indicates the possibility of a curved dimer (Figure F), and such a curved dimer had an improved fit to the solution scattering data (SI Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the straight SH3A domain-swapped dimer observed in the crystal structure of the p47phox–p22phox complex (pdb entry 1OV3 ) (Figure E) showed a better fit to the data, some discrepancies were still observed (SI Figure S1B). In the recent crystal structure of a p47phox–p22phox complex with an A200G mutation, the domain swapping is not present (pdb entry 7YXW ). Interestingly, in this structure the crystal packing indicates the possibility of a curved dimer (Figure F), and such a curved dimer had an improved fit to the solution scattering data (SI Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed no change in the dimer:monomer distribution when adding 5-fold excess of p22phox 149–168 during SEC analysis ( data not shown ) and existing p47phox–p22phox-peptide structures align well (1OV3, X-ray, dimer; 1WLP, NMR structure, monomer; 7YXW, X-ray, monomer) (Supporting Information Figure S4). ,, …”
Section: Resultsmentioning
confidence: 99%
“…In 2022, a structure-based design strategy allowed the development of the peptide-derived triproline mimetic compound 26 , which mimics an identified hot spot sequence (PPP) involved in the most important interactions with the p47 phox subunit. This derivative showed a submicromolar in vitro affinity ( K D of 0.312 μM) against the binding of the two subunits and could be further optimized to improve the affinity and drug-likeness …”
Section: Nox Inhibitorsmentioning
confidence: 99%
“…This derivative showed a submicromolar in vitro affinity (K D of 0.312 μM) against the binding of the two subunits and could be further optimized to improve the affinity and drug-likeness. 237 In 2015, Glaxo Smith Kline, in collaboration with the University of Geneve, carried out a high-throughput screening, followed by a lead optimization campaign, from which the 7azaindole 27 (GSK2795039) emerged. 238 The compound is reported as a competitive and selective inhibitor of NOX2 (pIC 50 value is 5.5 to 6.5, depending on assay performed) with more than 100-fold selectivity over xanthine oxidase and only 50% inhibition of eNOS at 100 μM.…”
Section: ■ Nox Inhibitorsmentioning
confidence: 99%
“…Several p22phox mimicking peptides ( Leto et al, 1994 ; Shi et al, 1996 ; Dahan et al, 2002 ; Drummond et al, 2011 ) and a few small-molecules have been reported as p47phox/p22phox inhibitors ( Figure 1B ). Recently, the polyethylene glycol (PEG)-based dimeric compound 1 ( Solbak et al, 2020 ) and the peptide-derived triproline mimetic 2 ( Garsi et al, 2022 ) were identified by fragment-based drug discovery and structure-based design, respectively. Both were shown to directly bind the SH3A−B domain of p47phox by surface plasmon resonance (SPR), and 1 inhibits the binding between a fluorescently-labelled p22phox peptide and p47phox SH3A−B in a cell-free fluorescence polarization (FP) assay.…”
Section: Introductionmentioning
confidence: 99%